Relevansi Ajaran Tasawuf Tehadap Pola Hidup Generasi Z - Mhd Rizky Rialdi Siregar; Hasnah Nasution; Hotmatua Paralihan (CV Edujavare Publishing, 2025)
The research titled “The Relevance of Sufi Teachings to the Lifestyle of Generation Z” aims to gain an understanding of the lifestyle of Gen Z. This study employs a qualitative research method using interviews, observation, and documentation. Sufism is an esoteric science in Islam, serving as a spiritual path that helps address inner diseases, loss of life’s meaning, and spiritual emptiness. Generation Z may be trapped in a consumptive and hedonistic lifestyle due to living amid strong currents of digitalization and social media. However, there are also members of Gen Z who show tendencies toward Sufi values such as zuhud (asceticism), shukr (gratitude), tawakkul (trust in God), and muhasabah (self-reflection), especially when supported by religious education and a positive spiritual environment. The findings of this study reveal that a contextual and creative Sufi approach through digital media, family environment, character education, and the role of religious figures can help shape a Gen Z character that balances worldly life with spiritual values.